Optical coherence tomography detects structural abnormalitiesof the nasal mucosa in patients with cystic fibrosis - Oltmanns, Ute; Palmowski, Karin; Wielpütz, Mark Oliver; Kahn, Nicolas; Baroke, Eva; Eberhardt, Ralf; Wege, Sabine; Wiebel, Matthias; Kreuter, Michael; Herth, Felix; Mall, Marcus A. (Journal of cystic fibrosis, 2016)
Background - Chronic inflammation and remodeling of the airways remain a hallmark of cystic fibrosis (CF). However, knowledge of the associated mucosal micro-anatomical changes is limited. We evaluated the potential of optical coherence tomography (OCT) for in vivo imaging of the upper airway mucosa in CF patients. - Methods - A flexible OCT probe was used for cross-sectional imaging of the nasal mucosa in 25 CF patients and 25 healthy controls. - Results - OCT images showed mucosal details including epithelium, basement membrane, lamina propria with seromucinous glands, and underlying cartilaginous structures. Mean nasal mucosa and epithelial layer thickness were increased in CF compared to controls. In CF patients, antibiotic therapy was associated with reduced nasal mucosa thickening. - Conclusions - OCT detected mucosal changes associated with upper airway inflammation and response to antibiotic therapy in CF patients. OCT may be a useful tool for quantitative in vivo assessment of structural changes of the airway mucosa.